Phyllobaeis Kalb & Gierl (Baeomycetaceae, Ascomycota) in Southern Brazil - Ana Clara Pereira; Andre Aptroot; Emerson Luiz Gumboski (Acta Biológica Catarinense, 2020)
Phyllobaeis is mainly a Neotropical genus and contains six species. It has a squamulose primary thallus (except for one species with crustose primary thallus), stipitate podetia, and simple or 1-septate hyaline, ovoid to fusiform ascospores. The species occur mainly on soil in altitudes of 700 to 4,400 m. In Brazil three species are known, recorded mainly from the southeast. The aim of this work is contributing to the knowledge of the distribution of Phyllobaeis in Brazil. We studied specimens from southern Brazil. The morphological, anatomical and chemical analyses follow standard lichenological protocols. We found two species in southern Brazil: Phyllobaeis erythrella, which is the first record to Paraná and Rio Grande do Sul states; and P. rubescens, which is the first record to Paraná and Santa Catarina states. Both occur in environments on the plateau, as well as in high-grasslands, between 700 to 1400 m altitude. A distribution map in Brazil, descriptions, figures and a key to the species of Phyllobaeis are given.